ANALISIS STRATEGI MANAJEMEN SMK DI SUKOHARJO SEBAGAI UPAYA PENGEMBANGANSDM PENGAJAR - sulistyadi, kohar (Universitas Sahid Surakarta, 2014)
School education is education that is obtained starting from kindergarten to university by a person in uniform , and systematic. Sudrajat (2008 ) describes the concept of school management as a process of school activities for the benefit of students , so that all the components including the utilization of all human resources directed schools to achieve effective management of the school .Â Sukoharjo government issued free school policy that began on January 2, 2007Â is expected to encourage increased public intellectual and fulfill the right to education and to realize the nine-year compulsory education program .Â To be able to develop the analysis it is necessary to study the effect of free school policy as a management strategy inthe development of vocational schools in Sukoharjo in order to create the hyuman resources Excellence